Residual Tumor Index: A Prognostically Significant Pathologic Parameter in Neoadjuvant-treated Pancreatic Ductal Adenocarcinoma. (November 2018) - Panni, Roheena Z.; Gonzalez, Ivan; Hartley, Christopher P.; Williams, Gregory A.; Liu, Jingxia; Hawkins, William G.; Chatterjee, Deyali
Abstract : In the setting of neoadjuvant therapy (NAT) for pancreatic ductual adenocarcinoma (PDAC), accurate measurement of tumor size, and consequently, staging based on AJCC eighth edition, is difficult. Attempts to address the limitations of tumor size in the NAT setting have included correlation of residual tumor percent with survival. However, only cases with complete pathologic response or minimal residual disease have shown better prognosis compared with all other groups. To date, no studies have simultaneously evaluated the prognostic value of tumor size and tumor regression in the setting of PDAC status post NAT (NAT-PDAC). Our aim was to study the prognostic value of residual tumor index (RTI), a metric combining residual tumor percent and tumor bed size as an interaction term (% residual tumor×tumor bed size [cm]). In a cohort of 105 cases of NAT-PDAC, we show that RTI supersedes the prognostic value of AJCC eighth edition T staging via multivariate cox regression. At a binary cutoff of 0.35 for RTI, the hazard ratio for recurrence-free survival is 3.26 (95% confidence interval, 1.51-7.04), P <0.01. We further identified cutoffs of ⩽0.2, 0.2 to 2 and >2 that stratified our cases into 3 groups via RTI, which were statistically significant in Kaplan-Meier curve analysis of recurrence-free survival ( P <0.01) and overall survival ( P <0.01). RTI represents a novel metric for combining the prognostic value of tumor size and residual tumor in NAT-PDAC.